Pengaruh Minat terhadap Kepuasan Khalayak (Studi pada Podcast PodHub di Kanal YouTube Deddy Corbuzier) - Meicella, Fioren; Aulia, Sisca (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Podcasts, with their on-demand nature, are a popular form of new media among Generation Z. Accessible via platforms like YouTube in audio-visual format, podcasts attract audiences with engaging and relevant content. One notable example is PodHub, a segment of Deddy Corbuzier's Close The Door podcast, hosted by Deddy Corbuzier and Vidi Aldiano. This research investigates the influence of audience interest on satisfaction with the PodHub podcast.Using the Uses and Gratification theory, the study applies a quantitative approach with purposive sampling and a questionnaire for data collection. The sample includes Generation Z individuals residing in Jakarta, aged 12–27, who actively listen to PodHub. The results reveal a strong positive relationship between interest and satisfaction. The correlation coefficient is 0.862, indicating a very high correlation, while the determination value of 74.4% confirms that interest significantly affects satisfaction. These findings highlight that relevant content, combined with an engaging communication style, enhances the audience’s experience. Interest plays a critical role in shaping audience satisfaction, demonstrating its importance in media consumption patterns. The research underscores how PodHub successfully meets the needs of its audience, emphasizing the potential of podcasts as a medium for delivering satisfying and meaningful content. Podcast dalam bentuk audio visual melalui saluran YouTube semakin banyak digemari khalayak. Salah satu contoh podcast yang populer di Indonesia adalah PodHub, bagian dari podcast Close The Door milik selebritis Deddy Corbuzier. Podcast ini dipandu oleh Corbuzier dan penyanyi Indonesia, Vidi Aldiano. Penelitian ini akan mengukur pengaruh minat terhadap kepuasan khalayak terhadap podcast PodHub. Penelitian ini menggunakan teori Uses and Gratification dengan pendekatan kuantitatif. Dengan teknik purposive sampling peneliti menyebarkan kuesioner dengan sampel generasi Z dengan rentang usia 12- 27 tahun berdomisili Jakarta. Penelitian menunjukkan terdapat pengaruh positif antara variabel dengan hasil uji koefisien korelasi menunjukkan nilai 0,862, artinya korelasi kedua variabel tersebut sangat tinggi. Nilai determinasi sebesar 74,4% menunjukkan adanya pengaruh antara variabel minat terhadap variabel kepuasan khalayak. Ketertarikan pada konten yang relevan, dan gaya komunikasi yang menarik mampu menciptakan pengalaman memuaskan bagi pendengar podcast PodHub.